2004
DOI: 10.1002/jgm.677
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in the IL‐2 signal peptide affects secretion of proteins in vitro and in vivo

Abstract: Modification of the IL-2 signal peptide augments protein secretion both in vitro and in vivo. As a result, optimizing the signal peptide should be considered for increasing the therapeutic levels of secreted proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 41 publications
0
68
2
Order By: Relevance
“…Additional modifications of the BMP-2 signal sequence led to loss of potency in secretion when altering the length of the sequence rather than altering specific amino acids. Therefore, previously described observations of enhanced potency of a secretion signal by increasing the basicity and hydrophobicity of the amino acid composition (Zhang et al, 2005) are in contrast to our results obtained after modifications of the BMP-2 secretion signal. One of the few candidates which displayed a potency to mediate protein secretion comparable to, or higher than, the native BMP-2 signal sequence was a signal sequence designed in silico (Z), consisting of a typical short basic region followed by a hydrophobic area combined with an in silico designed cleavage site.…”
Section: Figcontrasting
confidence: 99%
See 1 more Smart Citation
“…Additional modifications of the BMP-2 signal sequence led to loss of potency in secretion when altering the length of the sequence rather than altering specific amino acids. Therefore, previously described observations of enhanced potency of a secretion signal by increasing the basicity and hydrophobicity of the amino acid composition (Zhang et al, 2005) are in contrast to our results obtained after modifications of the BMP-2 secretion signal. One of the few candidates which displayed a potency to mediate protein secretion comparable to, or higher than, the native BMP-2 signal sequence was a signal sequence designed in silico (Z), consisting of a typical short basic region followed by a hydrophobic area combined with an in silico designed cleavage site.…”
Section: Figcontrasting
confidence: 99%
“…The secretion of proteins can be a limiting step if the native protein secretion signal is weak. The different potencies of secretion signals to drive protein secretion can be related to their amino acid composition (Futatsumori-Sugai and Tsumoto, 2010;Klatt and Konthur, 2012;Knappskog et al, 2007;Kober et al, 2013;Wen et al, 2011;Zhang et al, 2005). Based on this, the present study was expanded by the addition of screening and modification of protein secretion signals in order to identify signal peptide candidates with beneficial activity for subsequent exchange of the native BMP-2 protein secretion sequence.…”
Section: Introductionmentioning
confidence: 99%
“…Both leader sequences used in our studies did share those features. However, in the rat KC chemokine leader, the amino acid residues near the cleavage site have smaller side chains (Ser, Thr) than those of the H-2L d leader (Arg, Gln), which could account for its increased effectiveness (26,43). In conclusion, our findings demonstrate that leader sequences can be used to rationally design minigene DNA vaccines.…”
mentioning
confidence: 75%
“…Researchers showed that α-amylase, an enzyme native to the Bacillus stearothermophilus that degrades starch, can be secreted from mammalian cells by fusing a signal peptide 90 (METDTLLLWVLLLWVPGSTGD) derived from the murine Ig k-chain V-J2-C region [48,88]. Some of the commonly used secretion signals described in [8] are (i) ILCO1, which is an alteration of the interleukin-2 (IL-2) N-terminal signal peptide (ii) SS, which is the secretion signal originally derived from a piscine vitellogenin (Vtg) gene of Oreochromis aureus [88][89][90] (iii) Sec, which is a recently identified secretion signal that is a part of the C-terminal of the Engrailed-2 homeodomain protein present in Drosophila melanogaster. SEAP (Secreted Alkaline Phosphate) is naturally secreted from mammalian cells.…”
Section: (Vi) Type VI Secretion System (T6ss)mentioning
confidence: 99%